Wrongly “Identified”: Why an Actual Knowledge Standard Should Govern Health Care Providers’ False Claims Act Obligations to Report and Return Medicare and Medicaid Overpayments - Nicholas J. Goldin (Washington University Law Review, 2017)
In 2015, Medicare spent 632 billion on health care for America’s elderly (and other covered groups). Medicaid spent another 554 billion to provide health care to America’s needy. The government estimates that improper payments account for as much as 10% of Medicare and Medicaid spending. Given the vast amount of money at stake, and the fact that there is bipartisan support for recovering taxpayer dollars, it is no surprise the federal government has made it a priority to recoup the money lost to health care fraud each year. The results are noticeable: annual recoveries for health care fraud through the federal government’s most powerful anti-fraud weapon, the False Claims Act (FCA or “the Act”), have increased from 932 million in 2000 to a high-water mark of more than 3 billion in 2012. Health care providers now pay millions of dollars to settle allegations that they have committed health care fraud in violation of the FCA. . . This Note argues for the third approach, namely that overpaid Medicare and Medicaid claims should not be deemed “identified” until a health care provider has actual knowledge of their existence and amount. The Note is organized as follows: Part I introduces the relevant sources of law, including the FCA, the Sixty-Day Rule, and CMS’s regulations implementing the Sixty-Day Rule for Medicare. Part II describes a recent district court decision grappling with the proper interpretation of “identified” in the context of Medicaid overpayments, a situation in which none of CMS’s rules apply. Part III.A discusses how that case might be resolved if it dealt instead with claims under Medicare Part A or B, and thus were subject to CMS’s most recent regulation defining “identified.” Part III.B explains the problems with the existing regulatory scheme established by the FCA and current administrative interpretations of the Sixty-Day Rule. Part IV argues that providers should be required to have actual knowledge of overpayments for overpayments to be “identified.”
Keywords: Health law; Medicare; Medicaid; False Claims Act; Health care fraud; Sixty-Day Rule; Affordable Care Act; Healthfirst